Thermoelectrics design and materials - Lee, HoSung; Ebook Library (Chichester : Wiley, 2016)
Thermoelectrics: Design and Materials HoSung Lee, Western Michigan University, USA A comprehensive guide to the basic principles of thermoelectrics Thermoelectrics plays an important role in energy conversion and electronic temperature control. The book comprehensively covers the basic physical principles of thermoelectrics as well as recent developments and design strategies of materials and devices. The book is divided into two sections: the first section is concerned with design and begins with an introduction to the fast developing and multidisciplinary field of thermoelectrics. This section also covers thermoelectric generators and coolers (refrigerators) before examining optimal design with dimensional analysis. A number of applications are considered, including solar thermoelectric generators, thermoelectric air conditioners and refrigerators, thermoelectric coolers for electronic devices, thermoelectric compact heat exchangers, and biomedical thermoelectric energy harvesting systems. The second section focuses on materials, and covers the physics of electrons and phonons, theoretical modeling of thermoelectric transport properties, thermoelectric materials, and nanostructures. Key features: -Provides an introduction to a fast developing and interdisciplinary field. -Includes detailed, fundamental theories. -Offers a platform for advanced study. Thermoelectrics: Design and Materials is a comprehensive reference ideal for engineering students, as well as researchers and practitioners working in thermodynamics. Cover designed by Yujin Lee.
Thermoelectric generators -- Thermoelectric coolers -- Optimal design -- Thomson Effect, exact solution, and compatibility factor -- Thermal and electrical contact resistances for micro and macro devices -- Modeling of thermoelectric generators and coolers with heat sinks -- Applications -- Crystal structure -- Physics of electrons -- Density of states, Fermi energy, and energy bands -- Thermoelectric transport properties for electrons -- Phonons -- Low-dimensional nanostructures -- Generic model of bulk silicon and nanowires -- Theoretical model of thermoelectric transport Properties -- Appendix A: Physical properties -- Appendix B: Optimal dimensionless parameters for TEGs with Z2 = 1 -- Appendix C: ANSYS TEG Tutorial -- Appendix D: Periodic table -- Appendix E: Thermoelectric properties -- Appendix F: Fermi integral -- Appendix G: Hall factor -- Appendix H: Conversion factors.
Includes index.
Print version record.
Keywords: Thermoelectric apparatus and appliances -- Design and construction; Thermoelectric materials; TECHNOLOGY & ENGINEERING / Mechanical; Thermoelectric apparatus and appliances -- Design and construction; Thermoelectric materials; Electronic books